PEMBINAAN DISIPLIN SISWA SEKOLAH MENENGAH ATAS NEGERI KECAMATAN KOTO BARU KABUPATEN DHARMASRAYA - Wessy Rosesti (Jurnal Bahana Manajemen Pendidikan, 2014)
The aim of this research is to information about the Founding Of Student Dicipline. The population is 953 student and the sample is 143 people that taken by simple random sampling. The instrument of this research is question with likert scale models that had tested for validity and realibility. Data analyzed using mean score and performance level. The result of this research are the Founding Of Student Discipline Senior High School Of Koto Baru District  Dharmasraya  Regency stay in good category. Key word : Founding Dicipline